Kinetic and thermodynamic study of methylene blue adsorption using activated Syrian phosphate - مخايل, اميلي; إبراهيم راهب; حسام الركاد (Latakia University Journal -Basic Sciences Series, 2024)
Water pollution is one of the most important problems facing humans and the environment, as it takes place from many human activity forms, such as pollution with detergents, pesticides, petroleum materials, and organic dyes. The introduction of large quantities of dyes into the industrial wastewater led to chemical and biological changes. Therefore, many researches focused on finding ways to treat wastewater based on adsorption using low-cost natural materials with modifications by using the least possible amount of chemicals. This research was concerned with studying the possibility of removing methylene blue using activated Syrian phosphate using an acid / base treatment. The results showed that the adsorption process follows the langmuir model . and the adsorption value reached the maximum 20 mg/g .when analyzing the adsorption data kinetically , it was found that this process is subject to an apparent second-order reaction and has the value of rate constant 0.1 . Thermodynamic study showed that the process is exothermic ∆H = - 76.07 kj/mol and that the process is spontaneous at temperatures 25 and 35 c° .